Cytogenetic Effects of Individual and Combined Treatment of Cd2+, Cu2+ and Zn2+ in Vigna radiata (L.) Wilczeck - Alok Srivastava1; V.P. Singh1, Manoj Kumari1*, Vijay Kumar Sinhal2, (Journal of Phytology, 2011)
The present investigation has been designed to evaluate the cytogenetic effects of individual treatment of Cd2+ (0.2mg L-1), Cu2+ (6.5, 7.5 and 8.5mg L-1),and Zn2+ (6.3, 7.3 and 8.3mg L-1) and combined treatments of Cd2+ (0.2mg L-1) with Cu2+ (6.5, 7.5 and 8.5mg L-1) and Zn2+ (6.3, 7.3 and 8.3mg L-1) in two cultivars i.e.PDM-139 and K-851 of Vigna radiata (L.) Wilczek. The impacts of these doses were measured in terms of germination percentage, plant height, fresh and dry weight of plants, number and weight of root nodules, pollen and seed fertility, mitotic index and mitotic anomalies. The results showed that germination percentage, plant height, fresh and dry weight of plant, number and weight of root nodules, pollen and seed fertility, and mitotic index in both the cultivars were significantly reduced under the influence of all the individual treatment of heavy metals however, mitotic anomalies were enhanced. Cd2+ induced reductions in above mentioned growth parameters were significantly enhanced due to Cu2+ supplementation but such reductions were significantly recovered with Zn2+ supplementation. On the other hand, supplementation of Cu2+ increased the Cd2+ induced mitotic anomalies however Zn2+ supplementation was able to decrease the mitotic anomalies. It is clear from the present study that the individual treatments of Cd2+, Cu2+ and Zn2+ are toxic to both the cultivars of Vigna radiata (L.) andÃ‚Â the toxicity caused by Cd2+ is enhanced by Cu2+ supplementation but recovered by Zn2+ supplementation.